METHODICAL ASPECTS OF DETERMINATION OF THE BENTONITIC MOLDING CLAYS CHARACTERISTICS - N. N. Fedorov (Литьë и металлургия)
The features of different methods for determining the strength properties of bentonite molding clays are considered. It is shown that GOST 28177–89 not adequately characterizes the strength characteristics of bentonite important for its use in automatic molding lines. The expediency of mixing bentonite clays from different deposits, that allows to obtain a higher technological parameters of bentopowders in comparison with a variant of their manufacture from raw materials of one deposit is shown.